1998
DOI: 10.1159/000016496
|View full text |Cite
|
Sign up to set email alerts
|

In situ Fluoride Retention in Enamel and Dentine after the Use of an Amine Fluoride Dentifrice and Amine Fluoride/Sodium Fluoride Mouthrinse

Abstract: The aim of this in situ investigation was to study the effect of an amine fluoride/sodium fluoride mouthrinse (total F = 250 ppm) in addition to an amine fluoride dentifrice (F = 1,250 ppm) on the amount of acquired fluoride in enamel and dentine. In the partial prosthesis of 12 participants a combined specimen of slightly demineralized enamel and dentine was placed. During two consecutive experiments, each lasting 3 weeks, the participants used an amine fluoride dentifrice alone or in combination with a fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
17
1
2
Order By: Relevance
“…However, this difference was statistically significant only 90 min after toothbrushing when preceded by mouthrinsing after brushing [Attin and Hellwing, 1996]. High retention of fluoride after a fluoride mouthrinse and AmF dentifrice was found on enamel and dentine [van Strijp, 1999], and especially in lesions [ten Cate et al, 1988]. The present study indicates that AmF and AmF/SnF 2 can be incorporated into SRV while maintaining their antibacterial effect.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, this difference was statistically significant only 90 min after toothbrushing when preceded by mouthrinsing after brushing [Attin and Hellwing, 1996]. High retention of fluoride after a fluoride mouthrinse and AmF dentifrice was found on enamel and dentine [van Strijp, 1999], and especially in lesions [ten Cate et al, 1988]. The present study indicates that AmF and AmF/SnF 2 can be incorporated into SRV while maintaining their antibacterial effect.…”
Section: Discussionmentioning
confidence: 63%
“…Similar to our results Shani et al [2000] have also found that AmF has maintained high antibacterial activity although large amounts of bacteria were initially adsorbed onto HA saturated with an AmF solution. The high affinity of AmF to surfaces [Sefton et al, 1996;van Strijp, 1999], coupled with its relatively high affinity to bacteria, facilitates a strong killing effect of bacteria in a biofilm coated with AmF varnish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies testing fluoride therapy on demineralized enamel blocks have shown that fluoride content is dependent on the frequency of topical application. 12,23 One possible explanation for the difference observed between studies using previously demineralized enamel blocks versus sound enamel blocks submitted to cariogenic challenge may be that fluoride uptake in the latter experiments reached a plateau. According to Raven et al 24 the increased porosity and surface area of demineralized enamel increases its reactivity by allowing the fluoride to diffuse more readily into the enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Mouthrinses are usually recommended for active-caries patients in addition to normal use of fluoride dentifrice. 4 In vivo [6][7][8][9] and in situ studies [10][11][12] have shown that the frequency of topical fluoride applications is of importance to the effectiveness of caries preventive measures. Mouthrinses do not increase the fluoride exposure frequency, since they are usually applied immediately after the toothbrushing procedure.…”
Section: Introductionmentioning
confidence: 99%